Circular economy in the hospitality industry : awareness and implementation in Europe - Martins, Carina Soares (2021)
This thesis conceptualises and examines the Circular Economy in the Hospitality Industry. Sustainability has been a subject that has risen researches attention, as today’s environmental situation is aggravating on account of humans’ actions. The Hospitality Industry is considered to be in the spotlight of this issue as it is an important contributor to large waste generations. CE measures in the industry would minimise waste creation, yet this field lacks studies. For this purpose, an investigation on CE in the Hospitality Industry was made. For this research, a multiple case method was used to gather data. Interviews were made with different hotel operators from seven European countries to understand to what extent they are familiar with CE and if they integrate these measures in their operations. In general, the cases interviewed do not apply CE practices to a wider extent. The main practices carried out by the investigated hoteliers are related to basic recycling and reducing matters. Yet, one particular case stands out from the remaining cases, as it applies several CE practices intending to protect the environment. Given the complexity of this investigation and the difficulty to assemble a greater number of interviews, the responses gathered were limited and cannot be generalised due to different implications. For future research, it would be of high value to interview a greater number of participants to provide a more comprehensive and generalised study. Also, a survey would reach a higher number of participants.